Progressive fibrodysplasia osificans in pediatrics: about a clinical case (Salud, Arte y Cuidado, 2026)
Fibrodysplasia ossificans progressiva is one of the most unique and significant constitutional bone diseases, to the point of having been considered "the Mount Everest of musculoskeletal disorders of genetic origin." The scarcity of epidemiological data is a deficiency that FOP shares with all rare diseases. A clinical case is presented: an 11-year-old female adolescent, product of non-consanguineous parents, from a rural environment, with a history of cervical rectification diagnosed in the neonatal period, untreated, community-acquired pneumonia at 3 years of age, who required hospitalization for 7 days, left middle hearing loss and agenesis of the mastoid process diagnosed at 3 years by means of a brain magnetic resonance study; tonsillectomy at 5 years, without complications. SARS-CoV-2 infection in December 2021, empirically treated. Presenting, onset of the current disease in December 2021, after a mild SARS COV-2 infection, characterized by severe abdominal pain, worsening during walking, swelling of the abdominal and suprascapular muscles that limit flexion-extension is evident. cervical, its admission for multidisciplinary management is decided, in discussion, a probable diagnosis of Fibrodysplasia Ossificans Progressiva (FOP) is considered, deciding to carry out the respective bibliographic review
Keywords: Fibrodysplasia ossificans; Halluxvalgus; Heterotopic ossification